Pengaruh Managerial O wnership terhadap Firm Performance melalui Capital Structure sebagai Intervening pada Perusahaan Publik yang terdaftar dalam Bursa Efek Indonesia - Yenny Listiyani (Business Accounting Review, 2017)
This research aimed to examine the influence of managerial ownership on firm performance through capital structure as intervening on public companies listed in Indonesia Stock Exchange (IDX). This research used all sector of Indonesian public companies listed in IDX in the period of 2011-2015 excluding financial sector. Final sample was made from 373 firm years. Managerial ownership was measured by percentage of ownership owned by director and commissioner, capital structure was measured by debt to equity ratio and times interest earned ratio. While, firm performance was measured by Tobin’s Q, ROA, and ROE.The empirical result showed that managerial ownership had significant and negative affect towards both capital structure and firm performance. But, capital structure had significant and positive affect on firm performance. While the affect of managerial ownership toward firm performance through capital structure was significant and negative. The result showed that pecking order theory that used in decision making about sources of capital companies in Indonesia and managerial ownership was not suitable to be used in Indonesia to reduce the agency problem.